2005
DOI: 10.1002/pc.20097
|View full text |Cite
|
Sign up to set email alerts
|

Flax fiber surface modifications: Effects on fiber physico mechanical and flax/polypropylene interface properties

Abstract: This study arises on the opportunities of using flax fibers as reinforcement for polypropylene (PP) matrix composites. For this purpose, untreated flax fiber bundles obtained by a retting process have been used. For improving compatibility between flax fiber bundles and PP matrix, fiber surface treatments such as maleic anhydride, maleic anhydride polypropylene copolymer, and vinyltrimethoxy silane have been carried out. On the other hand, alkali treatment has also been carried out for fiber modification. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(82 citation statements)
references
References 46 publications
3
70
1
3
Order By: Relevance
“…It has been reported that alkalization improved the adhesive characteristics of a natural fiber surface by making the surface rougher and increasing the contact areas. 28,29) It is obvious from Fig. 1A that the 2% NaOH-treated wheat straw surface had the highest degree of roughness.…”
Section: Morphological Characterizationmentioning
confidence: 99%
“…It has been reported that alkalization improved the adhesive characteristics of a natural fiber surface by making the surface rougher and increasing the contact areas. 28,29) It is obvious from Fig. 1A that the 2% NaOH-treated wheat straw surface had the highest degree of roughness.…”
Section: Morphological Characterizationmentioning
confidence: 99%
“…Alkali treated fires called mercerization removes pectins and hemicellu-loses revealing highly clean separated fibers with a surface composition dominated by cellulose [42]. this treat-ment is known also to activate the OH groups of the cellulose [43], it's largely used to improve the mechanical properties of natural fibers used as reinforcement in composite materials [13] [14]. The PGUA, XG and cellulose thin films investigated in this work nicely model these three treatments.…”
Section: From Polysaccharide Model Surfaces To Real Flax Fibersmentioning
confidence: 76%
“…Such fibers have complex microstructure; they are composed by crystalline cellulose polysaccharide organized on several fibrils of around 10 nm diameter embedded in an amorphous matrix mainly composed of pectins and hemicelluloses. The cellulose fibrils constitute the layers of both primary and secondary cell walls [11] [12]; their unique structure, molecular organization and high crystallinity offer high strength to the flax fibers [13] [14]. The lumen cavity presented inside the secondary cell confers to the fibers a porous structure that makes them suitable for classical thermal insulation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, such suggestion could not really solve the problem. Also, there are always natural and artificial flaws or defects along the natural fibers, it is neither certain that the fiber failure will take place at the location having smallest cross-section area [15,16] since failure will possibly occur where the defect is situated during tensile test. For example, it has been reported that the probability of fiber break at minimum diameter was actually quite low, in the range of 40-60% [17].…”
Section: Challenges and Limitations Of Sftt Carried On Natural Fibersmentioning
confidence: 99%